Evaluation on the TBM Performance at a Hydropower Project in Ecuador (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
The aim of this manuscript is to discuss the Tunnel Boring Machine (TBM) performance along the recently constructed headrace tunnel of Minas-San Francisco Hydropower Project in Ecuador. Firstly, the manuscript briefly describes the importance of TBM tunneling and about the Minas-San HPP. Further, discussions are made on the engineering geological conditions along the headrace tunnel. Detailed evaluations are made on the performance of TBM tunneling considering influence of rock mass quality on the TBM penetration rate. The manuscript emphasizes that the knowledge of the rock mass quality parameters and cutter technology available at present are among the key factors that influence the estimation of the net penetration rate of the TBM. It has been demonstrated that the hard to very hard rock masses of high abrasivity that were encountered along the headrace tunnel alignment caused very low penetration giving slow progress, which was not predicted during planning phase design. The authors investigated a fairly good link between TBM penetration and the mechanical strength of the rock mass.